Dynamic Automobile Assembly Process using IOT - et. al., Krishnaveni Bukkapatnam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the wake of #AtmanirbharBharat and #MakeInIndia planks, there is a huge thrust to Manufacturing. This paper focuses on the Automobile Manufacturing process, enabling a customizable product, vis-a-vis a rigid Manufacturing process developed as per Industry 4.0 principles aided by IOT (Internet of Things) tools. The solution proposes to modularize entire Automobile Production/ Assembly Process, which simulates the whole process of the delivery to every customer through to the Manufacturer facilitates highly customized products based on dynamic user choices. Seamless integration of Networked Production Components is realized by building interfaces between existing ERP systems and MES (Manufacturing Execution Systems). The system adopts M3 - Modular Manufacturing Mode, via Wireless Networks for Industrial Automation - Factory Automation (WIA-FA) and Dynamic Control System, to Manufacture and Maintain Automobile Products at Scale. Proposed approach also improved Production Equipment utilization. Another aspect of this approach is flexibility of the Production/ Assembly Processes to enable high customization in product specification